Preparation and Investigation of a Novel Organic Polymer Consisting of 2,2,6,6-Tetramethylpiperidine-N-oxy as a Cathode Active Material in Li-Ion Batteries - Emre Biçer; Atilla Öktemer (International Journal of Electrochemistry)
In the present study, a novel organic polymer consisting of 2,2,6,6-tetramethylpiperidine-N-oxyl group as an electroactive center is employed by synthesizing it from a commercially ready polymer. An investigation on electrochemical and battery properties of this material as a cathode active material in different electrolyte salts was conducted. A coin cell shows a discharge capacity of 40 mAh g−1 at 1 C which is 76% of its theoretical capacity. It is observed that there is no significant decrease in capacity value even at 2 C and 5 C which indicates that it is applicable for the high-power applications. Besides, a good cycle stability is obtained with the organic radical battery.